2012
DOI: 10.1007/s00520-012-1667-5
|View full text |Cite|
|
Sign up to set email alerts
|

Identification of clinical predictive factors of oxaliplatin-induced chronic peripheral neuropathy in colorectal cancer patients treated with adjuvant Folfox IV

Abstract: Age, anaemia, hypoalbuminaemia, hypomagnesaemia and alcohol consumption are reliable and easily assessable clinical factors predicting incidence and length of oxaliplatin-induced neuropathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
64
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(73 citation statements)
references
References 12 publications
5
64
0
4
Order By: Relevance
“…The relationship with age is consistent with several previous reports of taxane-induced neuropathy, including ECOG 5103 (4, 8, 36). In contrast, a number of studies of oxaliplatin-treated patients did not find an association with age (6, 7). …”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…The relationship with age is consistent with several previous reports of taxane-induced neuropathy, including ECOG 5103 (4, 8, 36). In contrast, a number of studies of oxaliplatin-treated patients did not find an association with age (6, 7). …”
Section: Discussionmentioning
confidence: 78%
“…Unlike taxane-related CIPN, which can be reversible (2), cisplatin-induced peripheral neuropathy (CisIPN) can be cumulative and progressive and cause long-term effects on overall quality of life (QoL) and physical function (3). Studies have suggested that age, race, diabetes and obesity may be risk factors for CIPN (4, 5), but results have been conflicting (611). …”
Section: Introductionmentioning
confidence: 99%
“…Although these associations seem plausible, because such conditions can cause a neuropathy similar to CIPN, their role as risk factors for CIPN is not yet demonstrated since most previous investigations excluded these patients and the few existing studies have conflicting results [15][16][17][18] and, to our knowledge, the available results do not refer specifically to breast cancer patients.…”
Section: Introductionmentioning
confidence: 82%
“…Prädiktive Faktoren für das Auftreten einer oxaliplatinbedingten chronischen Polyneuropathie sind u. a. die kumulative Oxaliplatindosis (mit deutlich steigendem Risiko bei einer Gesamtdosis ≥ 800 mg Oxaliplatin/m 2 Körperoberflä-che), eine vorausgehende akute Neurotoxizität durch die Substanz, Anämie, Hypomagnesiämie, Hypalbuminämie sowie eine Körperoberflache von über 2 m 2 [5][6][7]. Beim KRK im UICC-Stadium III trat abhängig von der Dauer der adjuvanten Therapie mit Oxaliplatin und Fluoropyrimidinen eine chronische Polyneuropathie Grad II bei 2,3 % der Patienten, bei 3-und bei 3,9 % der Patienten bei 6-monatiger adjuvanter Therapie auf.…”
Section: Polyneuropathieunclassified